2007
DOI: 10.1002/app.26021
|View full text |Cite
|
Sign up to set email alerts
|

New thermosets obtained by cationic copolymerization of DGEBA with γ‐caprolactone with improvement in the shrinkage. II. Time–temperature–transformation (TTT) cure diagram

Abstract: Mixtures of diglycidylether of bisphenol A (DGEBA) with different proportions of g-caprolactone (g-CL) were cured with ytterbium triflate as initiator. The curing was studied with differential scanning calorimetry (DSC) and thermo mechanical analysis (TMA). The results are presented in the form of a time-temperature-transformation diagram. The kinetic analysis was performed by means of the isoconversional integral procedure and the kinetic model was also determined using the Coats-Redfern method. Gelation was … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
18
0

Year Published

2008
2008
2015
2015

Publication Types

Select...
8

Relationship

6
2

Authors

Journals

citations
Cited by 26 publications
(19 citation statements)
references
References 39 publications
1
18
0
Order By: Relevance
“…Equation (4) may be integrated employing Doyle's approach [28] and rewritten in logarithm form as shown by Equation (5) . This model has been previously determined for the resin/initiator system used in this work [30]. In this work it has been confirmed that the curing of PS-10/DGEBA formulations is also described by R 3 model.…”
Section: Theorysupporting
confidence: 74%
“…Equation (4) may be integrated employing Doyle's approach [28] and rewritten in logarithm form as shown by Equation (5) . This model has been previously determined for the resin/initiator system used in this work [30]. In this work it has been confirmed that the curing of PS-10/DGEBA formulations is also described by R 3 model.…”
Section: Theorysupporting
confidence: 74%
“…The linear integral isoconversional, model-free method of Kissinger-Akahira-Sunose (KAS) was used for the determination of the activation energy based on the nonisothermal curing curves [22,23] :…”
Section: Calorimetric Measurements (Dsc)mentioning
confidence: 99%
“…In addition, isothermal curing times determined by simulation of non-isothermal kinetic data (Equations (3) and (4)) were compared with experimental isothermal curing times obtained by means of FTIR experiments. Details of the kinetic methodology used can be found in previous works [21,22].…”
Section: Curing Kinetics (Dsc)mentioning
confidence: 99%